Langkah Awal Menuju Stabilitas Ekonomi pada Siswa SMA Swasta Nurcahaya Kota Medan - Fachrun Nissa; Nirma Rosalia; Retno Nela Simanjuntak; Muhammad Harpis (Lembaga Pengembangan Kinerja Dosen, 2025)
Individual economic stability is a crucial prerequisite for achieving well-being and financial independence. The Community Service Program (PKM) titled